Detection and documentation of modes of commission of service-related offences: methodology, tactics, digital traces, and the chain of custody - Serhieieva, D. B. (Аналітично-порівняльне правознавство, 2025)
It is indicated that official misconduct is characterized by high latency, institutional «embeddedness» in management procedures, and the ability to quickly adapt to changes in the regulatory environment. The article proposes an integrated forensic–procedural model for detecting and documenting modes of commission of service-related offences in a contemporary digital environment. Building on the systematization of forms of using or distorting official powers (abuse, excess of authority, intentional non-performance, bribery/undue advantage) and on typical “criminal technologies” (embezzlement through sham or intermediary contracts, deception-based appropriation, masking undue benefits as consulting/grants/charity, manipulations in EDMS/ERP/registries), the author develops an operational matrix “mode indicator → sources of information → tactical actions → procedural recording → standardized checklists.” The matrix enables a reproducible transition from reconstructing the mechanism of the event to practical algorithms: synchronized temporary accesses, examinations of electronic systems, inventories, graphing of payment chains, and verification of market equivalence. Special attention is paid to handling digital traces (metadata, version histories, access/approval logs, backups, correspondence) and maintaining an unbroken chain of custody (read-only imaging, hashing, environment description, access and transfer logs). A risk-based format of judicial control and standardized checklists for investigators, prosecutors, and investigating judges is substantiated to ensure necessity, proportionality, and procedural reproducibility. The paper also details how materials from operational-search activity and covert investigative actions are integrated into the evidentiary framework via “routing by mode indicator,” with data minimization and proper procedural incorporation. The novelty lies in coupling a criminological typology of modes with digital forensics and the procedural doctrine of admissibility/ reproducibility; the practical value is the standardization of the “first-day” response, introduction of “evidence passports,” and unified operational algorithms that increase evidentiary resilience in court.